A Case of Posterior Sternoclavicular Dislocation in a Professional American Football Player. (July 2015) - Yang, Justin S.; Bogunovic, Ljiljana; Brophy, Robert H.; Wright, Rick W.; Scott, Reggie; Matava, Matthew
Sternoclavicular (SC) dislocation is a rare injury of the upper extremity. Treatment of posterior SC dislocation ranges from conservative (closed reduction) to operative (open reduction with or without surgical reconstruction of the SC joint). To date, we are unaware of any literature that exists pertaining to this injury or its treatment in elite athletes. The purpose of this case report is to describe a posterior SC joint dislocation in a professional American football player and to illustrate the issues associated with its diagnosis and treatment and the athlete's return to sports. To our knowledge, this case is the first reported in a professional athlete. He was treated successfully with closed reduction and returned to play within 5 weeks of injury.